Relation of Various Anthropometric Measures and Nerve Conduction Velocity in Median Nerve - SHIREEN KHAWAR, MAHAM ZAHEER, BILAL, REEMA IRAM (Journal of Fatima Jinnah Medical University, 2018)
Background: Nerve conduction studies help to assess the different abnormalities of peripheral nervous system. It aids clinicians to distinguish the two main sets of peripheral diseases: axonal degeneration and demyelination Nerve conduction studies (NCS) which evaluate peripheral nerve functions and their parameters are known to differ with anthropometric measurements. Aims and Objectives: To study the effect of height, weight and Body Mass Index (BMI) on Compound Muscle Action Potential(CMAP) of median nerve. Materials And Methods: One hundred and twenty two, healthy first year medical students of Fatimah Jinnah Medical University were included in this study. The anthropometric factors (height, weight and BMI)was measured using standard technique. The compound muscle action potential (CMAP)of median nerve was recorded on power lab system. Result: The correlation between conduction velocity of median nerve and weight is very low that is -0.0921 and height is 0.074 and negative effect with BMI that is -0.121 Conclusion: Height weight and BMI did not show a significant correlation with the motor nerve conduction velocity (MNCV) of median nerve